Negotiation of Parental Duties in Chick-Rearing Common Murres (Uria aalge) in Different Foraging Conditions - Storey, Anne E.; Wilhelm, Sabina I.; Walsh, Carolyn J. (Frontiers in Ecology and Evolution, 2020)
Mates of biparental species share parental care but they are also predicted to try, within limits, to push for more offspring care from their partners. Here we test (a) whether mates will attempt to exploit their partners less often when resources are scarce so as to not push their partners to their abandonment threshold and (b) whether there are differences in exploitation and compensation strategies of low and high quality partners where the quality assessment is based on within-pair differences in chick-provisioning rates. The same fourteen pairs of common murres were observed in a year when capelin fish (the main prey species),were abundant (match year) and in a second year when capelin did not arrive inshore to spawn until the second week after hatching (mismatch year). One murre parent always attends the chick and, in the most common type of interaction, the returning parent feeds the chick and takes over the brooding role. We consider nest relief interactions to be irregular if they did not follow this sequence for determining which parent will continue or take on the lower-energy brooder role. Two types of irregular nest reliefs were examined: (a) the returning bird does not bring a fish and (b) the brooding bird does not allow a brooding changeover even when the returner brings a fish. Rates of irregular nest reliefs and total visit time increased in the mismatch year after capelin arrived inshore, suggesting that longer co-attendance in good conditions reflects negotiation, rather than the increased resting or ‘loafing’ time as previously proposed. High provisioners initiated fewer irregular nest reliefs than their low provisioning partners during favorable conditions but increased to comparable levels when resources were scarce. Partners’ attempts to brood without provisioning were less often refused during unfavorable feeding conditions, suggesting that murres compensated for their mates when they could. The observation that rates of irregular nest reliefs changed with resource availability suggests that negotiation occurs throughout chick rearing and is not a set ‘sealed bid’ at the onset.